Directional fatigue behaviour of maraging steel grade 300 produced by laser powder bed fusion. (August 2021) - Solberg, Klas; Hovig, Even Wilberg; Sørby, Knut; Berto, Filippo
Graphical abstract: Highlights: Investigation of the directional fatigue behaviour of PBF-LM/18Ni300. Proposal of a new test methodology for evaluating up- and down-skin fatigue. The fatigue behaviour is influenced by the specimen orientation. Fatigue initiation observed from up- and down-skin surfaces. Abstract: Surfaces of metals produced by additive manufacturing (AM) are known to be rough and populated with defects, this is, in particular, true for downward-facing (down-skin) surfaces. When dealing with the fatigue of as-built surfaces produced by AM, fatigue is typically initiating from surface defects. In this work, the fatigue behaviour of maraging steel grade 300 (18Ni300) produced by laser beam powder bed fusion (PBF-LB) is investigated. Fatigue initiation from surfaces built both up- and down-skin are investigated. This is done by using specimens where all surfaces are machined, except the one at interest. Specimens were built in 10 orientation ranging from 0° (horizontal, up-skin) to 135° (down-skin). The surface roughness was measured for all orientations; high surface roughness was found for down-skin surfaces while wavy surfaces were found for up-skin surfaces. The fatigue behaviour was found to be correlated to the build orientation and the surface roughness.